Small Chateau in Versailles Sebagai Inspirasi Baju Pesta Menggunakan Manipulating Cross Stitched Tucks - Ramadhani, Aliyyah; Prihatina, Yuhri Inang (Universitas Negeri Surabaya, 2025)
The purpose of this study was to 1) find out the process of making manipulating cross stitched tucks on party dresses inspired by the Small Chateau in Versailles, 2) find out the finished results of party dresses using manipulating cross stitched tucks. The Small Chateau in Versailles was used as a source of inspiration because the interior of the pavilion featured decorations using decorative elements in the form of manipulated cross-stitched tucks inspired by the design of the stairs in the pavilion. Using the Double Diamond research method, which consists of 4 stages, namely Discover collecting ideas and information and then compiling them into a moodboard as a reference in the design process, Define developing ten design concepts which were then selected and realized into one final design that was most representative, Develop presenting design illustrations and technical drawings that describe the concept of clothing in detail, the last stage Deliver ensuring that the resulting product has met the established quality standards. The results of the study showed that the use of this technique was able to add artistic and textural dimensions to party dresses, because manipulating cross-stitched tucks resembled the stairs in the pavilion, creating an exclusive and characteristic appearance. The resulting design is able to present an elegant classic feel through decorative elements and innovative textile manipulation techniques, while remaining relevant to today's style.